Reciprocal Tariffs in the Quest for Balanced Trade: A Zero-Sum Game for the WTO - Mavroidis, Petros (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional)

(untitled) (Société québécoise de droit international, 2025)
On April 2, 2025, President Trump announced “reciprocal tariffs” under the Fair and Reciprocal Plan, presented as a tool of trade justice to reduce deficits and restore balance. Duties were calculated on the basis of import and export volumes, later replaced by a flat 10% tariff for most partners and 25% on cars, with China facing the harshest treatment. The administration justified these measures as a way to cut trade deficits, combat drug trafficking, relocate production, finance social policies, and improve trade terms. The article argues, however, that tariffs are a blunt and ineffective instrument. Trade deficits are largely driven by United States fiscal imbalances, not foreign tariffs or other trade practices. Tariffs cannot replace border enforcement against trafficking, nor substitute for subsidies in industries. They are equally unrealistic as a tool for financing social policies. Moreover, costs are passed on to Unites States consumers and disrupt global value chains, harming United States industries themselves. Legally, the new tariffs breach US WTO commitments, violating bound duty levels and non-discrimination rules. Their effects extend beyond the Unites States: retaliation from partners like China, uncertainty in global markets, and discriminatory “deals” undermine the WTO system. Far from restoring reciprocity, these tariffs represent a unilateral assault on multilateral trade rules.